2015
DOI: 10.1016/j.sjbs.2014.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Development of interspecific Solanum lycopersicum and screening for Tospovirus resistance

Abstract: Tospovirus has emerged as a serious viral pathogen for several crops including tomato. The tomato production is being severely affected worldwide by Tospovirus. Some reports have been published about the association of plant virus and development of human disease either by direct or indirect consumption. Resistance to this virus has been identified as good source in wild tomato species (Lycopersicum peruvianum). But the introgression of resistance genes into cultivated tomato lines and the development of inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The search for natural resistance sources and resistance genes has intensified, and within the past three decades several resistance sources have been reported and incorporated into commercial tomato cultivars (35,46,102,106,108,119,120,129). Among these sources (40,93,108,128,130), recessive (sw2, sw3, and sw4) and dominant genes (Sw1a and Sw1b) have been reported; however, their resistance was quickly overcome upon challenging with TSWV (40,93,108,128,130).…”
Section: Natural Genetic Sources Against Tospoviruses For Tomato Breementioning
confidence: 99%
See 1 more Smart Citation
“…The search for natural resistance sources and resistance genes has intensified, and within the past three decades several resistance sources have been reported and incorporated into commercial tomato cultivars (35,46,102,106,108,119,120,129). Among these sources (40,93,108,128,130), recessive (sw2, sw3, and sw4) and dominant genes (Sw1a and Sw1b) have been reported; however, their resistance was quickly overcome upon challenging with TSWV (40,93,108,128,130).…”
Section: Natural Genetic Sources Against Tospoviruses For Tomato Breementioning
confidence: 99%
“…Therefore, an ongoing search for new tospovirus resistance genes remains essential in all breeding programs of tomato (35,46,102,106,108,119,120,129). More recently, 105 Solanum (section Lycopersicum: Solanaceae) accessions were evaluated for their reaction against TSWV, TCSV, CSNV, and GRSV isolates (33).…”
Section: A New Allele Of the Sw-5 Gene Cluster And Sw-5 Analogs In Otmentioning
confidence: 99%
“…These authors found that several crossing combinations with S. peruvianum made it possible to produce hybrid plants but that immature embryos needed to be cultured. The wild species S. peruvianum is resistant to TSWV (tomato spotted wilt virus), and tomato hybrids with S. peruvianum have been found to be resistant to this virus, which affects tomato production around the world (Sohrab et al 2015). The process of transferring genes from wild to cultivated species is often difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Managing orthotospoviruses poses a formidable challenge and this has received considerable attention due to their serious economic impact on crop production 2 . Extensive studies have attempted to engineer host resistance using partial or intact N gene sequences against orthotospoviruses which led to heritable immunity against homologous virus-species [11][12][13][14][15][16][17][18][19][20][21] . Further, RNAi approach has been demonstrated for development of transgenic against orthotospoviruses 22,23 including broadspectrum transgenic resistance 24 .…”
mentioning
confidence: 99%